Addressing engagement issues for interactive music technologies through a participatory design approach with 'SoundField'. (1st June 2015) - Deweppe, Alexander; Diniz, Nuno; Coussement, Pieter; Leman, Marc
This article presents a project that applies a collaborative design and an integrated evaluation approach to the bottom-up development of an immersive installation. In the inception of the set-up, user-related concerns for artistic technology-based applications were addressed in order to identify creative opportunities for the implemented multimodal technologies. For this purpose, an interdisciplinary collaboration between researchers from the arts, computer science and systematic musicology was established. Throughout a six-month project, a participatory and iterative design methodology was applied to the development of an augmented reality-based artistic installation. The project aimed at testing the flexibility of the technological platform, the artistic opportunities latent in the immersive installation domain, how users' cultural aspirations could be accommodated within the installation, how subjects with a standard media literacy were to engage with the technology at hand, and whether the quality of the experience could be improved by meeting the stated aesthetic requirements. The employed design strategy resulted in a user-inspired and use case-driven development process, in which gesturally controlled audio-visual features were tested, evaluated and improved for the entire duration of the project. Results include the delivery of 22 operational use cases in six different artistic application domains and the assessment of the applied methodology by means of the user-centred evaluation. In summary, SoundField's strategy of in-situ stakeholder involvement within the creative process allowed for following three: (1) successful implementations in a variety of cultural practices to be distilled, (2) limitations of the platform's interactive nature to be identified and (3) the rendition of guidelines for establishing user acceptance towards multimediated embodied interactive technologies.